Efficacy of Endodontic Treatment on the Persistence of Selected Endodontic Pathogens and on Radiographical Periapical Healing - Reyes Carmona DDS, MSD, PhD, Jessie; Ballestero DDS, Esp, Carolina; Hernández DDS. Esp, Erick; Ramírez DDS, MSD, Tatiana; Benavides DDS, Esp, Marianela; Meneses DDS, Esp, Pablo; Zeledón DDS, Esp, Rodolfo; Silva MQC, MSc, Sandra (Odovtos - International Journal of Dental Sciences, 2015)
The objective of this clinical study was to evaluate by polymerase chain reaction (PCR) the antimicrobial efficacy and the outcome of an endodontic protocol treatment (EPT) performed by under-graduated dental students on infected root canals associated with periapical lesions. Fifty-six patients attending for treatment of pulp necrosis and apical periodontitis were included. A specific EPT approach was performed and DNA extracts were taken at the baseline (S1), after a disinfection-neutralization procedure (S2), post-chemomechanical preparation (S3) and after Intracanal medication (S4) for the presence of specific bacteria. The outcome of the EPT was assessed radiographically using the Periapical Index-system (PAI) after 18-month follow-up. An intergroup evaluation shows that when comparing S1 to S3, S1 to S4, S2 to S3, and S2 to S4, the presence of bacteria were significantly reduced (P < 0.05). Finally, S4 was not significantly reduced when compared with S3 (P > 0.05). The most prevalent species in their respect order were Actinomyces Israelii > Enterococcus Faecalis > Fusobacterium Nucleatum/Prevotella Nigrescens > Phorphyromonas Endodontalis. After the 18-month follow-up, the overall success rate of root canal – treated teeth was of 88% (PAI 1 or 2). This In Vivo study demonstrated that EPT significantly reduced the number of cases with positive results for the studied bacteria, showing a profound positive impact in the outcome of endodontic treatment of teeth diagnosed with Pulp Necrosis and Apical Periodontitis.